Do protected areas increase household income? Evidence from a Meta-Analysis. (November 2022) - Kandel, Pratikshya; Pandit, Ram; White, Benedict; Polyakov, Maksym
Highlights: We conduct a global meta -analysis of 30 impact evaluation studies to estimate the protected area's impacts on local economic outcomes. Protected areas have positive and significant but smaller effect on local economic outcomes. Econometric method and study context affect likelihood and magnitude of protected area's impacts. Contextualized and targeted activities can generate greater and positive impacts of protected areas on local economic outcomes. Abstract: Do protected areas (PAs) increase or reduce the welfare of rural households? This study assesses this key question in environmental economics through a meta -analysis of studies that used income or poverty reduction as measures of welfare. A systematic search of peer-reviewed and "grey" literature identified 99 observations from 30 studies. The results showed that PAs have positive and significant impacts on economic outcomes at the local level, although the effect is small. The likelihood of observing positive economic impacts and the magnitude of the outcomes vary depending upon factors such as the choice of econometric method, location and context: studies from Africa are less likely to show positive welfare effects than studies from Asia and South America. Our findings contribute to research on the nexus between PAs and their economic impacts, and offer recommendations for researchers and practitioners working on this frontier.